Ekonomika, logistika a ekologie v ozbrojených silách 2 : International Conference Community - Army - Technology - Enviroment. Brno, Czech Republic (Vojenská akademie, 2001)
CATE 2001. Simulators and Simulations-Powerful Means for Training of Individuals and Crews of Combat Systems